THE IMPORTANCE AND BENEFITS OF SERVICE QUALITY IN TOURISM (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The tourism and hospitality industry is increasingly defined by its ability to meet and exceed customer expectations. With globalization and technological advancements, travelers now have access to a broader range of services and more information than ever before. In this context, service quality has emerged as a critical differentiator for tourism enterprises seeking to build loyalty, enhance reputation, and secure long-term profitability. This paper explores the theoretical foundations and practical applications of service quality in tourism, emphasizing the benefits that accrue economically, psychologically, and socially when high standards are maintained. Modern technologies are now performing many tasks traditionally carried out by service personnel: accepting online orders, registration, product evaluation, collecting feedback, and storing customer data. These processes are executed faster and more efficiently than manual labor. However, unlike other industries, in tourism and service, customer trust and communication play a more critical role.